Effect of angiotensin-converting enzyme inhibitors versus that of angiotensin receptor blockers on survival in patients undergoing hemodialysis: a nationwide observational cohort study - Seok Hui Kang; Gui Ok Kim; Bo Yeon Kim; Eun Jung Son; Jun Young Do (Renal Failure)
Background This study aimed to evaluate the patient survival rates based on the use of angiotensin-converting enzyme inhibitor (ACEI) or angiotensin II receptor blocker (ARB) in a large cohort of patients undergoing maintenance hemodialysis (HD).Methods Data from a national HD quality assessment program were used in this retrospective study. The patients were classified into four groups based on the use of renin-angiotensin system blockers (RASBs) as follows: No group, patients without a prescription of any anti-hypertensive drugs including RASBs; Other group, patients with a prescription of anti-hypertensive drugs excluding RASBs; ACEI group, patients with a prescription of an ACEI; and ARB group, patients with a prescription of an ARB.Results The 5-year survival rates in the no, other, ACEI, and ARB groups were 68.6%, 67.8%, 70.6%, and 69.2%, respectively. The ACEI group had the best patient survival trend among the four groups. In multivariable Cox regression analyses, no differences were observed between the ACEI and ARB groups. Among young patients and patients without diabetes or heart disease, the ACEI group had the best patient survival among the four groups. However, among patients with DM or heart disease, the ARB group had the best patient survival.Conclusions Our study found that patients receiving ACEI and ARB had comparable survival. However, patients receiving ARB had better survival in the subgroups of patients with DM or heart disease, and patients receiving ACEI had better survival in the subgroup of young patients or patients without diabetes or heart disease.